SIMULATION OF A SECURE COMMUNICATION SCHEME VIA HYBRID SYNCHRONIZATION OF CHAOTIC SYSTEMS WITH MINIMAL CONTINUOUS CHAOS - Oyeleke, Kehinde Solomon; Ojo, Kayode Stephen; Adeniji, Abidemi Emmanuel; Odumuyiwa, Victor T. (FUDMA Journal of Sciences, 2025)
This paper uses the Rossler attractor as a classical oscillator and presents a secure communication approach based on the hybrid synchronization of two identical chaotic systems via Lyapunov direct method. Equilibrium and bifurcation are two examples of fundamental dynamical features that are examined. A secure communication scheme is also presented based on synchronizing evolving chaotic systems with an uncertain parameter. The chaotic transmitter, the modulation, the chaotic receiver and the demodulation make up the communication scheme. The message signal is modulated into the system via the modulation process. Next, a public channel is used to transmit the chaotic signals to the recipient. The receiver end achieves synchronization between the transmitter and the receiver systems; and simultaneously estimates the unknown parameter through the design of the controller and parameter update law. The message signal is retrieved using the suitable demodulation technique and the detected parameter. To show the viability and validity of the described secure communication scheme, numerical simulations are performed.